2018
DOI: 10.21037/sci.2018.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the behavior of cultured sertoli cells in the presence and absence of spermatogonial stem cell

Abstract: The present study showed that removal of SSCs from the culture medium could be a model for damage to SSCs; the results revealed that niche cells respond to SSCs removal by upregulation of and to stimulate self-renewal of SSCs and abrogation of differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…bFGF appears to play a minor supportive role in SSC self-renewal because this factor alone cannot fully support the self-renewal of murine SSCs [21]. Interestingly, in vitro cocultivation experiments showed that the secretion of both GDNF and bFGF is upregulated in Sertoli cells in response to the withdrawal of SSCs from the culture [22]. in vivo , this mode of action could stimulate self-renewal and abrogate the differentiation of SSCs.…”
Section: Introduction To Mammalian Spermatogenesismentioning
confidence: 99%
“…bFGF appears to play a minor supportive role in SSC self-renewal because this factor alone cannot fully support the self-renewal of murine SSCs [21]. Interestingly, in vitro cocultivation experiments showed that the secretion of both GDNF and bFGF is upregulated in Sertoli cells in response to the withdrawal of SSCs from the culture [22]. in vivo , this mode of action could stimulate self-renewal and abrogate the differentiation of SSCs.…”
Section: Introduction To Mammalian Spermatogenesismentioning
confidence: 99%
“…Previous experimental studies postulate the role of testicular niche factors and Sertoli cells in regulating germ cell dynamics and maintaining testicular homeostasis [4,5,6]. However, the specific mechanisms regulating self-renewal and differentiation of spermatogonia in primates are not yet completely understood [7,8,9,10,11]. For understanding spermatogonial regulation in primates, establishing primate-specific in vitro approaches for co-culturing testicular germ cells and somatic cells isolated from adult testes are considered highly valuable.…”
Section: Introductionmentioning
confidence: 99%